Monstrøsitet som kulturel og religiøs diskurs: illustreret af monstertraditioner fra det gamle Mesopotamien - Feldt, Laura (Religionsvidenskabeligt tidsskrift, 2003)
The present contribution attempts to understand and interpret the significance of monstrosity, a well-attested phenomenon in the history of religions. First, monstrosity is interpreted as a mode of cultural discourse pertaining to boundaries and the construction of cultural categories. Its social function is understood along the theories of Girard. The presented view, however, suffers from a lack of adequacy. It neither explains the use of monsters in religious discourses, nor does it indicate why they are often used to bring about transformation and change. In addition to this, it does not offer an explanation for why monsters may be seen as positive and benevolent creatures.Second, the use of monsters in religious discourses is examined and monstrosity is interpreted in relation to Turner’s concept of liminality. The concept, however, is extended to include not only ritual sequences but also spatial and conceptual structures. In religious discourses, monsters can be seen as stigmatized pendlers between this world and ‘the other world’. It is claimed that monsters embody access to the transformative powers of transcendence and may thus be used both to ward off evil and to gain access to benevolence.In the last part of the contribution, these views are illustrated by an analysis of selected narrative and ritual monster traditions from the religions of ancient Mesopotamia. The examples document that monsters are not inherently evil creatures and that it makes sense to understand monsters in relation to boundaries and liminality. In religious discourses, monsters are used to focus on the relationship of humans to transcendence: preserving or obtaining blessing and life and warding off curse and death. Monsters are instruments for gaining access to transcendence, they are embodiments of liminality, and they are used to transform the existing order of things. Monsters dissolve differences and thereby thematize the possibility of change. In this manner, the use of monsters contributes to a questioning of fixed classifications and identities.